The controlling effect of sedimentary characteristics on the heterogeneity of the Chang 6 reservoir in the Wuliwan area - Zou, Xinzhe; Song, Xinmin; Wang, Youjing; Yan, Dezhi; Qin, Guosheng; Fang, Bo (Frontiers in Earth Science, 2024)
The sedimentary system of the delta front is complex. The hydrodynamic conditions, changes in sediment supply, and mineral composition are crucial factors that influence the quality of reservoirs. Reservoir quality varies among different sedimentary units. In this field of research, there is a general tendency to mainly use core data and logging curves for reservoir characterization and prediction, while neglecting the combination with the microscopic scale of the reservoir. This article proposes a new method to characterize reservoir heterogeneity by studying the sedimentary characteristics of reservoirs. This method uses casting thin-section data to aid in core and logging research. This study consists of five parts: core analysis, casting thin-section study, logging facies study, geological analysis, and single-well prediction. Combining macroscopic and microscopic methods helps clarify the controlling effect of sedimentary characteristics on reservoir heterogeneity. The research results indicate that this research method effectively solves the challenge of characterizing reservoir heterogeneity in the middle and later stages of development of low-permeability reservoirs. The research outputs serve as valuable references for the advancement of analytical matching fields.